036 No difference in long-term major adverse cardiac event rates between paclitaxel-eluting and sirolimus-eluting stents. (16th May 2012) - Abu-Own, H A; Jones, D A; Gallagher, S M; Rathod, K S; Jain, A K; Knight, C; Mathur, A; Wragg, A
Abstract : Background: Previous studies have demonstrated similar outcomes over the short to mid term in patients treated with paclitaxel-eluting stents (PESs) or sirolimus-eluting stents (SESs). However there is limited "real-world" data investigating long term outcomes. This study compared outcomes at 5 years following revascularisation in these two patient groups. Methods: 4252 consecutive patients underwent PCI with either paclitaxel-eluting (PES) or sirolimus-eluting stents (SES) at a single centre (October 2003–January 2011). Indications for PCI included stable and unstable angina. Left main and vein graft lesions were excluded. Demographic and procedural data were collected at the time of intervention. All cause mortality data were obtained from the Office of National Statistics via the BCIS/CCAD national audit out to a median of 4.0 years (95% CI 2.4 to 5.6 years). Primary end point was major adverse cardiac events (MACE) a composite of all cause mortality, myocardial infarction and target vessel revascularisation (TVR). Results: There were 1592 (37%) patients treated with SES and 2660 (63%) patients treated with PES. Baseline demographic, angiographic, and procedural characteristics were similar between patients treated with PES and those treated with SES. At 5 years, there were no statistical differences in MACE between the stent types (SES 15.9% 95% CI 12.7 to 19.4 vs PES: 16.5% 95% CI 12.6 to 20.3, p=0.9). This consisted of similar rates of all-cause mortality (10.1% vs 9.3%, p=0.4), TVR (5.3% vs 6.4%, p=0.4), and stent thrombosis (2% vs 1.8%, p=0.5). In diabetic patients (n=1172 (28%)), there was a trend towards lower MACE favouring PES but this did not reach statistical significance (19% vs 24%, p=0.16). On univariate and subsequent multivariate analysis there was no benefit from either stent type. Conclusion: This "real-world" observational analysis of DES-treated patients, PES and SES demonstrates similar overall safety and efficacy over a 5-year follow-up period with low rates of TVR.